The outcome of prenatal sonographic diagnosis of fetal talipes in the Cape Town Metro district - Swarts, Elfriede (Department of Obstetrics and Gynaecology, 2018)
Background: Talipes equinovarus, also termed club foot, is a congenital deformity of the ankle joint. Despite its prevalence of approximately 1 per 1000 live births, fetal talipes is relatively poorly studied since the introduction of percutaneous tendo Achilles tenotomies. Objectives: To document the associations, outcomes and prognosis of patients with antenatally diagnosed fetal talipes. The study aims to examine the association between, and prevalence of, fetal talipes and other abnormalities, structural and chromosomal, as well as the outcome in relation to postnatal surgery. The accuracy of prenatal ultrasound in diagnosing fetal talipes is also examined. Methods: A retrospective observational study was made of all cases presenting to the Fetal Medicine Unit between 1 January 2009 and 31 December 2014. All the identified cases were analysed to identify isolated talipes, associated abnormalities, and chromosomal abnormalities. The pregnancy outcomes were determined using the Astraia database as well as maternity records. When the outcome resulted in a live infant, these infants were followed up using the files at the referral hospital to determine the treatment method used and the number requiring surgery. Results: There were 155 cases, all referred to the Fetal Medicine Unit. Antenatal data included 75 who had other structural abnormalities and 75 who had isolated talipes. In five of the cases were no sufficient data could be found. Twenty-five cases were lost to follow-up, and 12 cases had no clubfoot at birth. Only one was labelled as having positional clubfoot. There were 91 live births. Of the cases of talipes with associated abnormalities, 21.19% were live births (excluding ENND). All terminations of pregnancy as well as 90.9% of intrauterine fetal deaths were complex talipes, and 94.52% of the cases of isolated talipes were live births. The most common associated abnormalities were of the central nervous system. Seventeen of the live births were lost to follow-up. Of the cases of isolated talipes, 53.19% had tenotomies and Ponseti treatment. The false positive rate of detecting fetal talipes on ultrasound was 7.74%. Conclusion: The study made it evident that complex talipes is associated with a poor pregnancy outcome defined as pregnancy loss, where isolated talipes is usually associated with a good pregnancy outcome. Ultrasound is a good diagnostic tool when diagnosing talipes antenatally but cannot diagnose the severity of the clubfoot. False negatives were not studied. The introduction of tenotomy can make a difference in the outcome of clubfoot in comparison with previous studies where tenotomies were not performed. Medical professionals need to address the importance of counselling, and a multidisciplinary team should be involved in cases involving prenatal counselling.